WRL-68 with the overexpression of CYP3A4 as an in vitro model to assess drug–drug interaction - Nurliana Abd Mutalib, Normala Abd Latip (Journal of Applied Pharmaceutical Science, 2021)
The drawback of using hepatoma cell lines such as HepG2 instead of the “gold standard” primary hepatocytes in studying in vitro drug metabolism is that the phase I metabolism enzymes, cytochrome P450 (CYP450), are poorly expressed with lower activities. The accuracy of predicting drug metabolism and interactions could be jeopardized with these limitations. Human hepatic cell line WRL-68 exhibits similar morphology with hepatic primary cultures and is highly potential to be developed as an in vitro tool for metabolism-based study. This study aims to develop the CYP3A4 overexpression in vitro cell-based model as an efficient tool for drug metabolism and interactions study. WRL-68 exhibits optimum liver marker gene expression and is most suitable for the overexpression model compared to HepG2 and Chang liver cell lines. CYP3A4 overexpression in the transiently transfected cell model was measured using quantitative real-time PCR. Over 2000-fold, CYP3A4 expression was achieved 48 hours after transfection and Western blot analysis further confirmed CYP3A4 overexpression. In addition, CYP450 reductase and cytochrome b5 expression in the cell model which are vital for CYP3A4 catalytic activity were found to remain intact after CYP3A4 overexpression. This model was also optimized for its testosterone 6β-hydroxylation activity (Km: 20.60 ± 0.10 µM; Vmax: 43.23 ± 1.21 nM/minutes/mg total protein) and thus proven to be a useful tool for in vitro drug metabolism and interaction study involving CYP3A4.
Keywords: WRL-68, CYP450, CYP3A4, metabolism, 6&beta; -hydroxylation, enzyme inhibition.